EFEKTIVITAS PENERAPAN UNDANG – UNDANG ITE DALAM TINDAK PIDANA CYBER CRIME - Rini Retno Winarni (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2016)
Crime in cyberspace is a growing problem both in terms of modus operandi as well as variety of crimes. The enactment - Law Number 11 Year 2008 on Information and Electronic Transactions (UU ITE) is expected to overarching legal issues, especially in the field of telematics, although we recognize that there are imperfections found in the law, therefore the need for revision of some articles. Rule of law can not be separated from law enforcement issues involving many parties. Therefore, the success of law enforcement is affected by things that in general there are several factors, namely the Act / regulations, factors law enforcement include those formed and those applying the law, a factor means or facilities to support law enforcement, community factors cultural factors as work, creativity and taste which is based on human initiative in social life. Accordingly, many factors that influence the effectiveness of a law lies in the professional and optimal role, powers and functions of law enforcement officials in their duties.